A VALIDATED RP-HPLC METHOD FOR THE DETERMINATION OF DILTIAZEM IN RAW MATERIAL AND PHARMACEUTICAL DOSAGE FORM (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
The objective of this work is to develop and validate a reverse phase high performance liquid chromatography (RP-HPLC) method for the quantitative analysis of Diltiazem in bulk and pharmaceutical dosage form. Chromatographic analyses were performed on RP C-18 column with a mobile phase consisting of 0.01M ammonium acetate in water, methanol and acetonitrile in the ratio 700:240:60 at a flow rate of 1 mL/min. The Diltiazem was detected and quantitated using a photodiode array detector at a wavelength of 295 nm with a retention time of 11.57 min. The detector response was linear in the concentration of 20-60µg/ml, the respective linear regression equation being Y=3000181x+356238.2. The limit of detection and limit of quantification were 0.5µg/ml and 0.15µg/ml respectively. The assay of Diltiazem in bulk was found to be 99.85%. From the recovery studies it was found that about 101% on average of Diltiazem was recovered which indicates high accuracy of the method. The method was validated by determining its accuracy, precision and system suitability.The method fulfilled the requirements for reliability and feasibility for application to the quantitative analysis of Diltiazem in bulk and pharmaceutical dosage form.